The Effect of Safety and Efficiency Levels on Land Transportation Public Transport Services - Retno Mawarti; Banun Erlin; Sarinah Sihombing; Yuliantini Yuliantini; Erny Sulistyaningsih (Dinasti International Journal of Education Management And Social Science, 2024)
This research is motivated by one of the choices of public transportation modes in East Jakarta is Damri Bus. The existence of Damri public bus transportation is expected to meet the mobility needs of people in East Jakarta and reduce congestion by integrating several urban transportation lines into one Damri bus line. The purpose of this study was to determine how the level of safety and efficiency affects public transportation services in East Jakarta (Damri). The method used in the research is quantitative research. The results of the study using SPSS 26. Shows that the level of safety has a significant and influential effect on land public transportation services (Damri) in East Jakarta. Efficiency has a significant and significant effect on public land transportation (Damri) in East Jakarta. The level of safety and efficiency has a significant effect on public land transportation services (Damri) in East Jakarta. This approach is relevant to evaluate Damri's contribution to improving the quality of public transportation as well as the safety of passengers and other road users.